S¹-Bott functions on manifolds - Repovš, D.; Sharko, V. (Український математичний журнал, 2012)
We study S¹-Bott functions on compact smooth manifolds. In particular, we investigate S¹-invariant Bott functions on manifolds with circle action. Вивчаються S¹-функцiї Ботта на компактних гладких многовидах. Зокрема, дослiджуються S¹-iнварiантнi функцiї Ботта на гладких многовидах з дiєю кола.